Profile of Colorectal Cancer Patients in Endoscopic Unit at Dr. Pirngadi Hospital - Medan - Rustam Effendi; Dasril Efendi; Leonardo Basa Dairy; Juwita Sembiring; Mabel Sihombing; Betthin Marpaung; Sri Maryuni Soetadi; Gontar Alamsyah Siregar; Lukman Hakim Zain (The Indonesian Society for Digestive Endoscopy, 2008)
Background: Colorectal cancer is the third most prevalent cancer and the second leading cause of cancer death worldwide every year. Rates of this malignancy vary by country. In Indonesia, the prevalence is estimated to have an increased tendency. The objectives of this sudy was to examine the prevalence and profile of colorectal cancer, which are diagnosed by endoscopic examination. Method: The study was conducted retrospectively, by examining the Result of endoscopic findings of patients with rectal bleeding, altered bowel habit, chronic diarrhea, unexplain abdominal pain, and other signs and symptoms at The Endoscopic Unit Department of Internal Medicine, Dr. Pirngadi hospital from January 2004 to June 2008. Results: We found 197 patients with colorectal cancer (CRC) from 760 patients examined by colonoscopy (25.9%). One hundred and one patients (51.3%) out of 197 CRC patients were female. Most were in the group of age 51-60 years (28.9%). The most frequent ethnic of the patients were Bataknese (46.2%). The most common symptom was rectal bleeding (70.6%). The most common location of CRC was in the rectum (74.6%). Histopathologic Result was adenocarcinoma. Conclusion: The prevalence of colorectal cancer in this study were twenty six percents. Rectal bleeding appeared to be the most common sign in this study. Rectum was the most common site of the cancer. Most of patients were Bataknese. Patients were at advanced stage and most of them were having well-differentiated adenocarcinoma. Keywords: colorectal cancer, rectal bleeding, altered bowel habits, colonoscopy